The use of metadiscourse in academic writing by Malaysian first-year ESL doctoral students - Lo, Yueh Yea; Othman, Juliana; Lim, Jia Wei (Universitas Pendidikan Indonesia, 2020)
Metadiscourse refers to linguistic items, which functions to establish a connection with imagined readers of a text (Hyland, 2004). The use of metadiscourse has received much attention in various contexts, yet, little works are focusing on disciplinary metadiscourse, that has been carried out. To address this gap, this study explored, described, and compared the use of disciplinary metadiscourse by eight Malaysian first-year ESL doctoral students across four areas of study in education. The study reported in this article focuses on development or changes in writing over time. This study is quantitative in nature with a corpus-based approach utilizing AntConc (3.4.4) to examine the frequency of three dimensions of academic discourse in their writing, namely textual, engagement, and evaluative The results of this analysis show that (i) the engagement dimension (3.1%) was the lowest of all three dimensions in written work, reinforcing the argument that first-year ESL doctoral students are less experienced at using textual metadiscourse resources, and (ii) frequency of all three dimensions of academic discourse in their writing differs across time between first written drafts to the final written drafts. These are first-year ESL doctoral students, who are writing in different fields of educational research. The implication is that teaching and learning of disciplinary metadiscourse should involve explicit explanation, demonstration, and practice of its use, and development in the academic writing process.Academic writing; corpus analysis; ESL doctoral students; metadiscourse